Diagnostic methods and treatment of ADHD in children: A review (International Seven Journal of Health Research, 2024)
INTRODUCTION: Attention deficit hyperactivity disorder (ADHD) is classified as a neurodevelopmental disorder that affects several children. It is a public health problem and is characterized by behavioral changes of inattention, hyperactivity, and impulsivity. OBJECTIVES: In view of the relevance of the theme, the present study aims to address the diagnostic methods and treatment of ADHD in children. METHODOLOGY: The work was developed from an integrative literature review, through searches in the Virtual Health Library (VHL) and SciELO databases. The following words were chosen as guiding terms for the search: "ADHD", "Children", "Clinical Diagnosis" and "Treatment Protocol". RESULTS: Early diagnosis is of paramount importance for treatment and prognosis. For the child to be diagnosed with the disorder, he must have a persistent pattern of inattention and hyperactivity and treatment is done through efficient non-pharmacological measures, such as cognitive behavioral therapy. CONCLUSION: It is important that the diagnosis is made correctly to provide the child with a good quality of life and reduce the impacts and symptoms of the disorder.